A Restructured Hospital Into a One-Building Organization for COVID-19 Patients: A Resilient and Effective Response to the Pandemic - Bessis, Simon; Dinh, Aurélien; Gautier, Sylvain; Davido, Benjamin; Levy, Jonathan; Lawrence, Christine; Lot, Anne-Sophie; Bensmail, Djamel; Rech, Célia; Farcy-Afif, Muriel; Bouchand, Frédérique; de Truchis, Pierre; et al. (Frontiers in Public Health, 2022)
The COVID-19 pandemic is a unique crisis challenging healthcare institutions, due to a large influx of patients, rapidly overwhelming hospitals. This major event forced all the components of the healthcare systems to adapt and invent new workflows. Our tertiary care hospital was entirely reorganized. During the cruising phase, additional staff was allocated to a one-building organization comprising an intensive care unit (ICU), acute care unit, physical medicine and rehabilitation unit, and COVID-19 screening area. The transfer of patients from a ward to another was easy and fast due to these organizations and pavilion structure. We deplore only few deaths in acute care ward, except in the palliative unit. No nosocomial infection with SARS-CoV-2 was reported in any other building of the hospital since this organization was set up. This type of one-building organization, integrating all the components for comprehensive patient care, is the most appropriate response to pandemics.